Lean Logistics of the Transportation of Fresh Fruit Bunches (FFB) in the Palm Oil Industry - Cheah, Cheng Teik; Fernando, Yudi (IGI Global USA, 2018)
The purpose of this paper is to assess the efficiency, effectiveness and performance of logistics in transportation of Fresh Fruit Bunches (FFB) in Malaysian estates which are the growing logistics hubs in plantation management. It also identifies various factors that significantly affect the efficiency, effectiveness and performance of the Malaysian estate logistics and proposes ways to improve their competitiveness. This study shall empirically explore the causal relationships between Lean Logistics and Triple Bottom Line on Sustainable Logistics Performance in transportation of FFB in the Palm Oil Industry. The objective is to examine the current state of sustainability efforts within the field of value chain, more specifically logistics performance, and to identify opportunities and provide recommendations for the palm oil industry to follow sustainable performance. This study also aims to stimulate further research within the area of sustainable logistics performance.